Forms of forfaiting - Adam Karbowski (Munich Personal RePEc Archive, 2021)
In the following note, the concept of forfaiting as well as various forms of forfaiting are discussed. The following criteria are used to distinguish different forms of forfaiting - type of financial instrument that secures a receivable, placing of risk, additional services, number of parties to a transaction, territorial range. Based on those criteria, specific forms of forfaiting are briefly characterised.
Keywords: F3; G2; 330; forfaiting; international trade